ANALISIS PENGARUH BUDAYA ORGANISASI, KEPUASAN KERJA DAN KEPEMIMPINAN TERHADAP KOMITMEN ORGANISASI ( StudiPadaKaryawan Kantor Wilayah Bank BRI Semarang ) - Baraweri, Syaiful Ahmat; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2015)
The success of the organization to achieve its goals and objectives is largely depend on employee commitment. Employees who are highly committed see them selves as a true member of a company, ignoring minor source of discontent. Organizational commitment are influenced by many factors, such are organizational culture, job satisfaction and leadership. The purpose of this is study on to analyze the influence of organizational culture, job satisfaction and leadership is organizational commitment.Population in this study are employees of the Regional Office of Bank Rakyat Indonesia (Persero) Semarang, Jl. Teuku Umar No. 24, Semarang, with the total of respondents 237. The samples in this study were 70 employees.Non random sampling techniqul was utilized in this study. Data were colleected through questionnaire distribution. The analysis technique used is multiple regression. Results of analysis using SPSS shows that :Organization culture have significant effect on organizational commitment. Job satisfaction have significant effect on organizational commitment. Leadership have significant effect on organizational commitment.